The self‐assessed psychological comorbidities of prurigo in European patients: a multicentre study in 13 countries. (12th July 2018) - Brenaut, E.; Halvorsen, J.A.; Dalgard, F.J.; Lien, L.; Balieva, F.; Sampogna, F.; Linder, D.; Evers, A.W.M.; Jemec, G.B.E.; Gieler, U.; Szepietowski, J.; Poot, F.; et al.
Abstract: Background: Prurigo is defined by the presence of chronic pruritus and multiple localized or generalized pruriginous lesions. Objective: The aim of this study was to assess the psychological burden of prurigo in patients of European countries. Methods: In this multicentre European study, 3635 general dermatology outpatients and 1359 controls were included. Socio‐demographic data and answers to questionnaires (regarding quality of life, general health, anxiety and depression and suicidal ideation) were collected. Results: There were 27 patients with prurigo; of these, 63% were men, and the mean age was 58.6 years. Among patients with prurigo, 10 of 27 (37%) suffered from anxiety and 8 of 27 (29%) from depression. Suicidal ideation was reported in 5 of 27 (19%) patients, and for four of these five patients, suicidal ideation was related to their skin disease. These frequencies were higher in the 10 commonest dermatological diseases (including psoriasis, atopic dermatitis and leg ulcers). The impact on quality of life was severe, with a mean Dermatologic Life Quality Index (DLQI) of 12.4, with an extreme impact on quality of life for 23% of patients and a very large impact for 27% of patients. Conclusion: The psychological comorbidities of prurigo are common, greater than those of other skin diseases, and their impact on quality of life is significant. Thus, it is important to study this condition and to find new treatments.